Erythromelanosis follicularis faciei et colli - A cross-sectional, descriptive study - Shagufta Rather; Atiya Yaseen; Mani Mukhija (Wolters Kluwer Medknow Publications, 2016)
Background: Erythromelanosis follicularis faciei et colli (EFFC) has always been reported as a rare disorder, and more data are needed to define its etiology and epidemiology. Objectives: To present a descriptive study of this disorder from Kashmir and present a review of literature on the same. Materials and Methods: A cross-sectional, descriptive study was conducted on 14 patients with clinical lesions suggestive of EFFC, presenting to our dermatology outpatient clinic between May 2013 and April 2015. After obtaining informed consent from all patients, the demographic and clinical data were collected and punch biopsies were taken which after being fixed in formalin were stained for hematoxylin and eosin. The study was approved by Institutional Review Board. Results: Age of the patients ranged from 12 to 35 years with a mean age of 24.8 years. Females outnumbered males in a ratio of 1.3:1. Family history was positive in one case, and one patient had unilateral presentation. The classical triad of erythema, pigmentation, and follicular papules were present in 100% patients. Telangiectasias were observed in 28.57% patients only. Classical sites described were involved in all the cases (100%). In addition, lesions were found to involve eyebrows (28.57%), forehead (28.57%), upper lips (14.28%), and pinna (21.42%). Keratosis pilaris was present in all patients (100%); most common sites affected were upper arms and thighs. Two (14.28%) had generalized distribution. Histopathology in all correlated well with clinical findings. Conclusion: EFFC has always been reported as a rare disorder, but we believe that it is not so. The reason could be either lack of awareness of the disease by the patient due to its generally asymptomatic nature or under-recognition by the physicians. Awareness about the disease on part of dermatologist and recognition of clinical presentation is important for correct diagnosis and to help find more effective therapeutic modalities.